1981
DOI: 10.1139/m81-195
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring prototrophic strains of Salmonella typhi

Abstract: In a survey of the nutritional requirements of Salmonella typhi it was found that 3.2% of 560 recent clinical isolates were able to grow in a minimal medium consisting of phosphates, ammonium and magnesium sulfates, and glucose; the remainder required tryptophan. Both groups grew slowly and rather poorly in these media due to a deficient utilization of sulfur from sulfate. Addition of cysteine or sodium sulfide or thiosulfate promoted rapid and profuse growth. Minimal medium containing thiosulfate as a source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Surprisingly, this included facile availability of all three aromatic amino acids based on full virulence of auxotrophic Salmonella pheA tyrA trpA . This was also consistent with common tryptophan auxotrophy of Salmonella enterica serovar Typhi clinical isolates from human typhoid fever patients [64]. On the other hand, aromatic amino acids were previously thought to be unavailable in infected mouse tissues based on strongly attenuating mutations in chorismate biosynthesis [65], [66], a precursor for aromatic amino acids.…”
Section: Discussionsupporting
confidence: 78%
“…Surprisingly, this included facile availability of all three aromatic amino acids based on full virulence of auxotrophic Salmonella pheA tyrA trpA . This was also consistent with common tryptophan auxotrophy of Salmonella enterica serovar Typhi clinical isolates from human typhoid fever patients [64]. On the other hand, aromatic amino acids were previously thought to be unavailable in infected mouse tissues based on strongly attenuating mutations in chorismate biosynthesis [65], [66], a precursor for aromatic amino acids.…”
Section: Discussionsupporting
confidence: 78%
“…The results of this study provide explanations for a number of observations regarding the resilience of S. enterica as a facultative intracellular pathogen. Acquisition of host-derived cytosolic peptides as a source of carbon units and amino acids would explain the observation that clinical isolates of Salmonella often harbor amino acid auxotrophies or defects in carbon source utilization, yet they remain virulent and pathogenic for both animals and humans (18,19,70). Recent studies have also shown that intracellular Salmonella are able to evade the host autophagy response as an innate immune mechanism of pathogen clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in vitro and in vivo have indicated that access to glucose and related sugars is important for full virulence in the host; however, these same studies have also indicated that none appear to be essential (11,12,(15)(16)(17). Indeed, the majority of clinical isolates of S. typhi, the causative agent of human typhoid, are auxotrophic for amino acids and show highly variable capacities for carbon source utilization (18,19). Furthermore, highly attenuated aroA strains of S. typhimurium recover virulence in mice when metabolites not involved in aromatic amino acid biosynthesis but whose synthesis also require chorismate are included in feed or water (20).…”
mentioning
confidence: 99%
“…Such a concept has been postulated for the reactivation of infection in the case of chronic infections caused by an E. coli hemB mutant (45). Finally, it should be noted that in the specific case of serovar Typhi, a hostadapted serovar that triggers chronic and asymptomatic infections in humans, many clinical isolates are auxotrophs for aromatic amino acids (55). Altogether, these observations indicate that a more profound molecular analysis of S. enterica SCV isolates is necessary, which may provide clues about whether switching to a stable SCV phenotype has consequences for Salmonella pathogenesis.…”
Section: Discussionmentioning
confidence: 99%